Factors influencing healthy menopause among immigrant women: a scoping review - Ping Zou; Thumri Waliwitiya; Yan Luo; Winnie Sun; Jing Shao; Hui Zhang; Yanjin Huang (BMC, 2021)
Abstract Background Many factors influence the menopausal transition and the complexity of this transition increases with the addition of immigration transition. This review aims to identify the factors that influence the menopausal transition for immigrant women based on ecosocial theory. Methods A scoping review of English publications was conducted according to PRISMA guidelines using CINAHL, AgeLine, MEDLINE, PsycINFO, ERIC, Nursing and Allied Health Database, PsycARTICLES, Sociology Database, and Education Research Complete. Thirty-seven papers were included for this review. Results The factors which influence the menopausal transition for immigrant women were grouped into three categories: (a) personal factors, (b) familial factors, and (c) community and societal factors. Personal factors include income and employment, physical and psychological health, perceptions of menopause, and acculturation. Familial factors include partner support, relationships with children, and balancing family, work, and personal duties. Community and societal factors encompassed social network, social support, healthcare services, traditional cultural expectations, and discrimination in host countries. Conclusions Interventions addressing the menopausal transition for immigrant women should be designed considering different psychosocial factors and actively work to address systemic barriers that negatively impact their transition.